Optimalisasi pemberdayaan kesehatan dalam implementasi dermatitis di Desa Sungai Alat, Kecamatan Astambul, Kabupaten Banjar - Martini Naibaho; Asni Hasaini; Muhlisoh (Universitas Mataram, 2022)
Implementation community service in Astambul District, Sungai Alat Village, Dermatitis disease the 6th highest. Unclean environmental conditions, prone to flooding have resulted in Residents of Sungai Alat village being susceptible dermatitis. Objective to implement dermatitis screening Villagers Sungai Alat, Local health workers follow up and explain to cadres how dermatitis screening. Etiology of Dermatitis is not known with certainty, there is an interaction Intrinsic and Extrinsic Factors Dermatitis. Symptoms include itching and skin disorders according specific morphology and distribution. So far there no follow up. Short interviews with 10 villagers, 8 people said that they often experience itching, redness in the hands, feet, ranging from children, adults, the elderly. Itching on skin experienced, because they not realize causes, whether was due allergy to something or fungus. Based on the data above, proposing team wants to improve health status of the community and achieve a better standard of living. Strategy improve quality of health services, one of conducting initial dermatitis screening residents Sungai Alat village, Service Team cadres in the village to screen dermatitis, making easier Residents to get health services. Method implementation use the existing dermatitis hand tool. Assessment is carried out by looking condition of residents' skin and matching with a hand tool, if appropriate, then validate/confirm by asking that have been determined. Activity involved all villagers of Sungai Alat, students and proposing team. Results Activities that will be provided form screening data and data for cadres who can carry out screening stages properly.